Trametinib therapy for children with neurofibromatosis type 1 and life‐threatening plexiform neurofibroma or treatment‐refractory low‐grade glioma. (3rd May 2021) - Ronsley, Rebecca; Hounjet, Celine D.; Cheng, Sylvia; Rassekh, Shahrad Rod; Duncan, Walter J.; Dunham, Christopher; Gardiner, Jane; Ghag, Arvindera; Ludemann, Jeffrey P.; Wensley, David; Rehmus, Wingfield; Sargent, Michael A.; et al.
Abstract: Purpose: To describe a series of children with extensive PNF or treatment refractory PLGG treated on a compassionate basis with trametinib. Methods: We report on six patients with NF‐1 treated with trametinib on a compassionate basis at British Columbia Children's Hospital since 2017. Data were collected retrospectively from the patient record. RAPNO and volumetric criteria were used to evaluate the response of intracranial and extracranial lesions, respectively. Results: Subjects were 21 months to 14 years old at the time of initiation of trametinib therapy and 3/6 subjects are male. Duration of therapy was 4–28 months at the time of this report. All patients had partial response or were stable on analysis. Two patients with life‐threatening PNF had a partial radiographic response in tandem with significant clinical improvement and developmental catch up. One subject discontinued therapy after 6 months due to paronychia and inadequate response. The most common adverse effect (AE) was grade 1–2 paronychia or dermatitis in 5/6 patients. There were no grade 3 or 4 AEs. At the time of this report, five patients remain on therapy. Conclusion: Trametinib is an effective therapy for advanced PNF and refractory PLGG in patients with NF‐1 and is well tolerated in children. Further data and clinical trials are required to assess tolerance, efficacy and durability of response, and length of treatment required in such patients. Abstract : Here, we report on response to Trametinib, a MEK inhibitor in children with NF‐1. Our experience presented in this report demonstrates that Trametinib is an effective therapy for advanced, life‐threatening PNF, and treatment‐refractory PLGG in patients with NF‐1 and is well tolerated in children.